Intermittent versus continuous incremental field tests: Are maximal variables interchangeable? - Carminatti, Lorival Jose (2013)
The aim of the present study was to compare physiological responses derived from an incremental progressive field test with a constant speed test i.e. intermittent versus continuous protocol. Two progressive maximum tests (Carminatti's test (TCAR) and the Vameval test (T-VAM)), characterized by increasing speed were used. T-CAR is an intermittent incremental test, performed as shuttle runs; while T-VAM is a continuous incremental test performed on an athletic track. Eighteen physically active, healthy young subjects (21.9 ± 2.0 years; 76.5 ± 8.6 kg, 1.78 ± 0.08 m, 11.2 ± 5.4% body fat), volunteered for this study. Subjects performed four different maximum test sessions conducted in the field: two incremental tests and two time to exhaustion tests (TTE) at peak test velocities (PV). No significant differences were found for PV (T-CAR = 15.6 ± 1.2; T-VAM = 15.5 ± 1.3 km·h-1) and maximal HR (T-CAR = 195 ± 11; T-VAM = 194 ± 14 bpm). During TTE, there were no significant differences for HR (TTET-CAR and TTET-VAM = 192 ± 12 bpm). However, there was a significant difference in TTE (p = 0.04) (TTET-CAR = 379 ± 84, TTET-VAM = 338 ± 58 s) with a low correlation (r = 0.41). The blood lactate concentration measured at the end of the TTE tests, showed no significant difference (TTET-CAR = 13.2 ± 2.4 vs. TTET-VAM = 12.9 ± 2.4 mmol·l-1). Based on the present findings, it is suggested that the maximal variables derived from T-CAR and T-VAM can be interchangeable in the design of training programs. © Journal of Sports Science and Medicine.